An outlook on printed microsupercapacitors: Technology status, remaining challenges, and opportunities - Nicolosi, Valeria (My University, 2020)
The concept of the Internet of Things is dramatically changing the way society interacts with physical spaces and portable technologies. For the last couple of years, intensive research has been devoted on the design of several flexible and even wearable devices, such as displays and health-care sensors. Further developments on these new technologies are heavily conditioned by the lack of compatible energy storage/conversion units. Contrary to lithium-ion batteries, supercapacitors can be easily miniaturized and integrated on flexible/wearable technologies without losing their electrochemical performance. In this review, some of the most recent developments on the design and printing of light, flexible, and thin microsupercapcitors along with promising and further practical applications are presented.
Keywords: microsupercapcitors; Internet of Things (IoT); lithium-ion batteries; Printed microsupercapacitors; Flexible technology; Smart textiles; Energy storage/conversion